Igniting the "Family Sacrifice": Cotton Mather and Familial Christian Education in Puritan New England. Issue 2 (November 2014) - Setran, David
In his preaching and writing, Puritan pastor Cotton Mather compared family religion to a "family sacrifice." This image anchored a vision of home nurture that highlighted both the offering of family spiritual practices and the offering of family members themselves as "living sacrifices" in their everyday lives. Mather's vision of sacrificial family faith formation resulted in an approach that was holy and grace-filled, personal and corporate, formal and informal, and strong and submissive.